2022
DOI: 10.1186/s12877-021-02722-9
|View full text |Cite
|
Sign up to set email alerts
|

Frailty-aware care: giving value to frailty assessment across different healthcare settings

Abstract: Healthcare systems need to adapt to better serve an aging population with complex presentations. Frailty assessments are a potential means to address this heterogeneity in aging to identify individuals at increased risk for adverse health outcomes. Furthermore, frailty assessments offer an opportunity to optimize patient care in various healthcare settings. While the vast number of frailty assessment tools available can be a source of confusion for clinicians, each tool has features adaptable to the constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 123 publications
0
41
0
2
Order By: Relevance
“…Therefore, frailty can be used to identify people at risk of poor outcomes such that they can be streamed into frailty-attuned pathways of care, and doing so might provide early information for person-centred and decision-making discussions. 7 Tools to measure frailty fall into two broad paradigms: either a phenotypic model, characterised by weight loss, self-reported exhaustion, weakness, slow walking, and low physical activity, 8 or a deficit accumulation model in which the more health issues accrued, the more likely a person is to have poor reserve. 9 A recent systematic review identified 13 studies in which frailty had an effect on mortality after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, frailty can be used to identify people at risk of poor outcomes such that they can be streamed into frailty-attuned pathways of care, and doing so might provide early information for person-centred and decision-making discussions. 7 Tools to measure frailty fall into two broad paradigms: either a phenotypic model, characterised by weight loss, self-reported exhaustion, weakness, slow walking, and low physical activity, 8 or a deficit accumulation model in which the more health issues accrued, the more likely a person is to have poor reserve. 9 A recent systematic review identified 13 studies in which frailty had an effect on mortality after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the sociodemographic questions revealed importance. According to other studies, sociodemographic variables, namely, age and gender, are significant features [ 16 , 40 ]. Furthermore, in another recent study, age was the most important variable in predicting 90-day mortality and the second-most important variable for 30-day mortality [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to implementing frailty screening in clinical settings still exist as a lack of consensus on the assessment tool best suited to each domain and undetermined cost-effectiveness [ 16 ]. Moreover, it is imperative to note that the frailty assessment tools can provide different data regarding the incidence of frailty [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in peripheral androgen and estrogen play an important role in the onset, recurrence and progression of the majority of breast cancers [ 39 ], and also in the pathophysiology of frailty syndrome [ 40 , 41 , 42 , 43 ], along with other factors such as inflammation and metabolic disorders [ 44 , 45 , 46 ]. The identification of biomarkers that could help clinicians to identify patients that develop frailty syndrome or suffer worsening of frail syndrome would facilitate clinical decision making and reduce adverse outcomes related to frailty [ 47 , 48 , 49 ]. As expected, during AROi treatment the concentration of estrogen in blood decreased due to aromatase inhibition [ 50 , 51 ], as evidenced in our study by the decrease in the aromatase activity index, the reduction of estrone (the main estrogen in postmenopausal women) [ 52 , 53 ] and the increase in androstenedione (the precursor of estrone) [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%